The Role of Organizational Culture in Improving Public Services Study of the One-Stop Administration Office Salak Pakpak Bharat Regency - Ismail Fahmi Harahap; Syafruddin Ritonga; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
The challenge of the role of organizational culture in improving public services for Samsat Salak, Pakpak Bharat Regency, North Sumatra Province. Seen from the number of taxpayers who deliberately disobey and awareness of taxpayers. This study aims to explain the role of organizational culture, supporting factors and service approaches in Samsat Salak, Pakpak Bharat Regency. This study uses a descriptive qualitative approach using a phenomenological paradigm, the research location is the Salak Samsat Office, Pakpak Bharat Regency, North Sumatra Province. The results showed that the role of community leaders was very influential and kinship in obedience to paying vehicle taxes. The service approach was not maximized due to limited human resources in the implementing section, mobile Samsat facilities were not available. This causes people to pay taxes on holidays such as Lebaran and New Year. Despite being fined. The number plate replacement service is not effective, the process must be in Medan so that it can raise suspicion and seem less serious about the government in maintaining public services